Le corps numérique des données - Tiziana Nicoletta Beltrame (Ateliers d'Anthropologie)
The transfer of extra-European collections from the Museum of Man to the Musée du quai Branly involves the displacement of documentary information on the artefacts. The various paper files (on collections or inventory, descriptive of the object, methodological) created and classified within different departments of the Museum of Man are being replaced by digital files, or “TMS objects”, at the Musée du quai Branly. The information is not simply changing its location and material, it is being reconfigured within new interconnections of knowledge on the collections. The museum inventory is here conceived as the system that materialises a structured knowledge. To be able to analyse this system, it is necessary to link the documents’ properties to the methods used to classify them in an ad hoc space. The materiality of the media, the multiple possibilities for storage and for the creation of links (linking components of digital files) affect the contents of data and thus open new avenues for the construction of knowledge.